Pengaruh Intensitas Sosialisasi Kebijakan Pemerintah Terhadap Tingkat Partisipasi Masyarakat Dalam Program Pengelolaan Sampah Di Kota Palangka Raya - Gusti Nazarudin; Natanael Meiky Victorius Samalukang; Bhayu Rhama; Imanuel Jaya (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
The problem of waste management in Palangka Raya City is still a strategic issue along with the increasing volume of household waste which reaches ±150 tons per day. The City Government through the Environmental Service (DLH) has issued a number of policies and programs, including the establishment of a Waste Bank and policy socialization activities to the community. However, the level of community participation in waste management programs is still relatively low. This research aims to analyze the influence of the intensity of socialization of government policies on the level of community participation in waste management programs in Palangka Raya City. The research method uses a quantitative approach with the type of explanatory research. The research population is people who follow the waste management program in Palangka Raya City with sampling techniques (adjusted, for example: proportional random sampling). Data is collected through a questionnaire with a Likert scale and analyzed using simple linear regression. The research results show that the intensity of policy socialization has a positive and significant effect on the level of community participation. That is, the more frequent, clear, and interactive socialization is carried out, the higher the level of community participation in supporting waste management. This finding emphasizes the importance of the role of intensive and sustainable policy communication in realizing waste governance based on government and community collaboration.